Analisis Pemahaman Calon Guru Sekolah Dasar tentang Nilai Karakter Bangsa pada Mata Kuliah Konsep Pendidikan Karakter - Rahmadani, Ervi; Bungawati (Jurnal Ilmu Pendidikan Dasar Indonesia, 2022)
The purpose of this study was to describe the understanding of elementary school teachers candidates’ on the value of national character in the Character Education Concept course. This study uses a descriptive method with a qualitative approach. The population in this study were all active 2020 PGMI students, totaling 89 people. The sampling technique used is random sampling, namely members of the population are selected randomly so that the number of samples consisting of 49 people is obtained. The instrument used in this research is in the form of a questionnaire distributed to the respondents. The results showed that the average student understanding of character values ​​in the Character Education Concept course was 89% which was in the very good category.